Step
*
1
1
1
of Lemma
assert-init-seg-nat-seq
1. n : ℕ
2. k : ℕ
3. s : ℕn ⟶ ℕ
4. r : ℕn + k ⟶ ℕ
5. n ≤ (n + k)
⊢ ↑equal-upto-finite-nat-seq(n;s;r) 
⇐⇒ ∃h:finite-nat-seq(). (<n + k, r> = <n, s>**h ∈ finite-nat-seq())
BY
{ ((Thin (-1) THEN (Assert n + k ∈ ℕ BY Auto)) THEN (RWO "assert-equal-upto-finite-nat-seq" 0 THENA Auto)) }
1
1. n : ℕ
2. k : ℕ
3. s : ℕn ⟶ ℕ
4. r : ℕn + k ⟶ ℕ
5. n + k ∈ ℕ
⊢ s = r ∈ (ℕn ⟶ ℕ) 
⇐⇒ ∃h:finite-nat-seq(). (<n + k, r> = <n, s>**h ∈ finite-nat-seq())
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  k  :  \mBbbN{}
3.  s  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}
4.  r  :  \mBbbN{}n  +  k  {}\mrightarrow{}  \mBbbN{}
5.  n  \mleq{}  (n  +  k)
\mvdash{}  \muparrow{}equal-upto-finite-nat-seq(n;s;r)  \mLeftarrow{}{}\mRightarrow{}  \mexists{}h:finite-nat-seq().  (<n  +  k,  r>  =  <n,  s>**h)
By
Latex:
((Thin  (-1)  THEN  (Assert  n  +  k  \mmember{}  \mBbbN{}  BY  Auto))
  THEN  (RWO  "assert-equal-upto-finite-nat-seq"  0  THENA  Auto)
  )
Home
Index